A thermodynamic study of CO2 sorption and thermal transition of PolyActive™ under elevated pressure. (14th June 2016) - Rahman, Md. Mushfequr; Lillepärg, Jelena; Neumann, Silvio; Shishatskiy, Sergey; Abetz, Volker
Abstract: The sorption of CO2 in two commercial grades of multiblock copolymers (PolyActive™) is investigated using a magnetic suspension balance in the temperature range 30–70 °C. The isotherms follow Henry's law when the poly(ethylene glycol) (PEG) blocks of PolyActive™ are in a molten state. A significant deviation is observed when the PEG blocks are still in a semicrystalline state. Differential scanning calorimetry (DSC) is used to study the thermal transitions of the polymers. The melting and crystallization of the PEG blocks is studied using high pressure differential scanning calorimetry in both CO2 and N2 gas environment. A substantial decrease of melting and crystallization temperatures occurs with increasing CO2 pressure. But no change occurs under N2 pressure. The observed experimental results are discussed on the basis of established thermodynamic equations reported in the literature which provide an adequate guideline to correlate the sorption isotherms with the thermal transition of the PEG blocks. Graphical abstract: Highlights: CO2 sorption behavior of commercial PolyActive™ multiblock copolymer. When PEG block is semicrystalline sorption isotherms deviate from Henry's law. Thermal transition of PEG block with increasing CO2 and N2 pressure. Melting point depression of PEG block occurs with increasing CO2 pressure. Melting point depression causes deviation from Henry's law for CO2 sorption.